College Student Reactions to Holocaust Education From the Perspective of the Theme of Complicity and Collaboration. (July 2020) - Aalai, Azadeh
A colloquium series funded by the National Endowment for the Humanities explored complicity and collaboration during the Holocaust at a community college in New York. Student reactions to this theme were explored to measure their understanding of this atrocity. Twenty-three student participants of this colloquium submitted to in-depth, in-person interviews. A descriptive qualitative process enabled the researcher to identify specific themes that emerged regarding student growth. Student reflections explore the extent to which Holocaust education enables transformational learning at the college level, specifically in this case by exploring bystander behavior. Challenges of Holocaust education may be confronted by developing a focus for students to use as a framework. Results suggest a framework facilitates student growth and enrichment. This study is a reflection on practice regarding exposure to the Holocaust in higher education and its potential to stimulate transformation.